Prognostic stratification in venetoclax-based acute myeloid leukemia treatments: the molecular prognostic risk signature tested in a real-world setting - Gaia Ciolli; Matteo Piccini; Francesco Mannelli; Giacomo Gianfaldoni; Barbara Scappini; Laura Fasano; Francesca Crupi; Elisa Quinti; Andrea Pasquini; Jessica Caroprese; Giada Rotunno; Fabiana Pancani; et al. (Haematologica, 2024)
Not available.